Religione e guarigione: libertà religiosa e principio di autodeterminazione in materia di salute mentale (salus aegroti suprema lex o voluntas aegroti suprema lex) (Stato, Chiese e pluralismo confessionale, 2019)
SOMMARIO: 1. Linee di lettura - 2. La guarigione forzata: i fatti di Vilnius - 3. Il percorso giudiziario che conduce alla decisione di Strasburgo - 4. La dissenting opinion: brevi appunti sul metodo -5. Il sofferto cammino della libertà religiosa tra fede, stregoneria e follia - 6. La forza terapeutica della libertà religiosa: “capacità-libertà” di credere e diritto di guarire - 7. La funzione politica della religione in terra lituana: semi di neo-confessionismo - 8. La sfida dell’inclusione dell’altro da sé: scelte etero-spirituali e prudentia iuris.Religion and healing: religious freedom and the principle of self-determination in matters of mental health (Salus aegroti suprema lex o voluntas aegroti supremaABSTRACT: The case before the Court of Strasbourg, projects us into the most sacred and private dimension of the life of the human being: that of religious options. In the present case, a young woman with behavioral disorders, manifested even before joining the group close to the Movement founded by the Indian Master Osho, following undergoes a series of medical treatments obligatory that force her to the suspension of the religious practices to which she usually devotes for her own psychophysical well-being. But according to the opinion of the doctors these practices compromised the applicant's mental health status, representing a serious and ascertained danger. The doctor becoming the promoter of his patient's health, ends up interfering in the personal sphere of the girl's religious sentiment, trying to modify the choices deemed to be non-conforming to tradition and prejudicial to health, without scientific evidence and, exclusively, on basis of presumptions and religious prejudices. The facts give rise to some considerations on the methods and criteria for balancing the protection of the right to health, and self-determination in therapeutic choices, and the exercise of religious freedom in conditions of compromised mental health, and the risk of a reviving confessional in Lithuania.